2000 IEEE International Conference on Multimedia and Expo. ICME2000. Proceedings. Latest Advances in the Fast Changing World Of 2000
DOI: 10.1109/icme.2000.869652
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive QoS for mobile multimedia services over wireless networks

Abstract: Absfrucf-A wireless network that provides multimedia services should control the quality of the transmission link for users, allocating resources according to the service type of each user, be it voice, video, image or data. This paper proposes a scheme to allocate the desired signal to interference noise ratio (SINR) for those users with multimedia services by exploiting power control and smart antennas, while not affecting users with voice service. A method to quickly initialize new users into such a network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Due to the nature of multimedia data, we can assign higher SINR intervals to substreams that require higher rates and lower SINR intervals to those which require lower rates (such as a video substream as opposed to an audio substream). We have shown that the optimization problem: is NP-hard [7]. The part that makes this problem intractable is the second line of (9), which is the test for feasibility of r.…”
Section: Rate Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the nature of multimedia data, we can assign higher SINR intervals to substreams that require higher rates and lower SINR intervals to those which require lower rates (such as a video substream as opposed to an audio substream). We have shown that the optimization problem: is NP-hard [7]. The part that makes this problem intractable is the second line of (9), which is the test for feasibility of r.…”
Section: Rate Controlmentioning
confidence: 99%
“…If the number of antenna elements, D, in the antenna arrays is large enough so that we can assume that the effect of S I k , J ( -) in ( 3 ) can be neglected, then the signal to noise ratio for the ith substream of user k , is [7] (1 For simplicity, assume we use PSK, then the probability of bit error conditioned on the SINR is P r ( e r r o r 1 y k ) = Q ( e ) , which we shall denote p e , k . Here, Q(z) = & J e T d t .…”
Section: Rate Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been considerable attention devoted to this subject, where the term QoS has been used as an epithet for a variety of quality measures, such as packet dropping rate [1], [2], bit-error rate [3], resolution or quantization scale [4], packet delay [1], [5], and [6], bandwidth [3], [6], and [7], or channel quality or signal-to-interference and noise ratio (SINR) [8]. In this paper, the performance index will be the SINR levels [9], [10].…”
mentioning
confidence: 99%